What are healthcare providers’ understandings and experiences of compassion? The healthcare compassion model: a grounded theory study of healthcare providers in Canada - Sinclair, Shane (BMJ Open, 2018)
BACKGROUND: Healthcare providers are considered the primary conduit of compassion in healthcare. Although most healthcare providers desire to provide compassion, and patients and families expect to receive it, an evidence-based understanding of the construct and its associated dimensions from the perspective of healthcare providers is needed. OBJECTIVES: The aim of this study was to investigate healthcare providers’ perspectives and experiences of compassion in order to generate an empirically derived, clinically informed model. DESIGN: Data were collected via focus groups with frontline healthcare providers and interviews with peer-nominated exemplary compassionate healthcare providers. Data were independently and collectively analysed by the research team in accordance with Straussian grounded theory. SETTING AND PARTICIPANTS: 57 healthcare providers were recruited from urban and rural palliative care services spanning hospice, home care, hospital-based consult teams, and a dedicated inpatient unit within Alberta, Canada. RESULTS: Five categories and 13 associated themes were identified, illustrated in the Healthcare Provider Compassion Model depicting the dimensions of compassion and their relationship to one another. Compassion was conceptualised as—a virtuous and intentional response to know a person, to discern their needs and ameliorate their suffering through relational understanding and action. CONCLUSIONS: An empirical foundation of healthcare providers’ perspectives on providing compassionate care was generated. While the dimensions of the Healthcare Provider Compassion Model were congruent with the previously developed Patient Model, further insight into compassion is now evident. The Healthcare Provider Compassion Model provides a model to guide clinical practice and research focused on developing interventions, measures and resources to improve it.